THE RELATIONSHIP BETWEEN KNOWLEDGE AND MATERNAL EDUCATION IN COMPLIANCE WITH PENTAVALENT IMMUNIZATION IN INFANTS AGED 0–11 MONTHS: A CROSS SECTIONAL STUDY - Nesa Ayu Murthisari Putri; Elis Desmawati (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Pentavalent immunization is an important program in reducing infant morbidity and mortality, but immunization coverage is still not optimal, which is thought to be influenced by maternal knowledge and education factors. This study aims to determine the relationship between maternal knowledge and education levels and compliance with pentavalent immunization in infants aged 0–11 months. The research method used an analytical survey design with a cross-sectional approach conducted at the Tanjung Agung Community Health Center UPTD in April 2026 with a sample of 141 mothers selected through formula calculations and inclusion and exclusion criteria. Data were collected using questionnaires and analyzed univariately and bivariately using the Chi-Square test with a significance level of 5%. The results of the study showed that most mothers were non-compliant in providing immunizations (56%), had low knowledge (63.1%), and low education (52.5%). There was a significant relationship between knowledge and compliance (p = 0.002) and between education and compliance (p = 0.000) where mothers with higher knowledge and education tended to be more compliant in providing pentavalent immunization. In conclusion, there is a significant relationship between maternal knowledge and education levels and compliance with pentavalent immunization in infants. It is recommended that community health centers (Puskesmas) provide education to mothers about the importance of pentavalent immunization in infants aged 0-11 months.